What is community justice? case studies of restorative justice and community supervision - Karp, David R., 1964-; Clear, Todd R.; Sage eBooks (Thousand Oaks, Calif. ; London : Pine Forge, 2002)
As described in this title, the aim of the new efforts is to explicitly integrate the community and the criminal justice process in probation programs. There are five goals that this text addresses to achieve this end.
Specialized.
Description based on print version details on publisher's website; title from home page (viewed on Mar. 19, 2012).
Keywords: Community-based corrections -- United States; Restorative justice -- United States; Electronic books